Konsep Manajemen Pengelolaan Sarana dan Prasarana dalam Menunjang Proses Pembelajaran - Ishak Ishak; Nasrudin Harahap; Nurul Hidayati Murtafiah (Departement of Mathematics Education, 2023)
This study expects to analyze all the more profoundly the idea of the board of offices and framework the executives in supporting the growing experience. This study utilized subjective exploration strategies. The information involved by the creators in this study is a wellspring of information that is pertinent and has likenesses with the conversation being examined. The technique for gathering information in this study is Library Exploration. The consequences of the exploration show that the administration of offices and foundation in supporting the educational experience should be overseen appropriately. Also, instructive framework is extremely valuable and assumes a significant part in supporting the smooth running of the instructive cycle since despite the fact that the instructing and learning exercises are great, they are not upheld by instructive devices or foundation, the outcomes accomplished won't be just about as wonderful true to form. Thus, regard for the administration of all offices and framework or hardware in schools should be focused on for the acknowledgment of the principal objective of having this gear to have the option to help outcome in learning.